Prevalence and factors associated with survival of cardiac arrest among in-hospital adult patients -an utstein style reporting from a tertiary hospital in east coast of Malaysia - Razak, Hafizul Asrar Abdul Razak (2020)
Introduction: In-Hospital Cardiac Arrest (IHCA) commonly happens in every hospital throughout the world. Very few studies were done regarding this matter compared to out of hospital cardiac arrest (OHCA) especially in Malaysia. The purpose of the study is to determine the prevalence of IHCA in a tertiary hospital located in the East Coast of Malaysia, and to identify any associated factors. Methods: This was a retrospective cross-sectional study involving all IHCA cases from 1st January 2012 until 31st December 2017 using the Utstein Style as its template for data collection. Data were analysed with simple and multiple logistic regression. Result: A total of 308 patients have been recruited and 286 sample have been analysed. Our study showed that most of the patients who developed IHCA were in the age group of 60-69 years old with the mean age of 58. The events of IHCA happens mostly during the day (56.7%), mainly due to non-cardiac causes (69.1%) with the most common initial rhythm of asystole (65.2%). Multiple logistic regression analysis showed that the presence of mechanical ventilation was significantly associated with ROSC (p < 0.001). Conclusion: The prevalence of ROSC in the East Coast region of Malaysia is higher (55.8%) compared to that of other developing countries and the use of mechanical ventilations are associated with ROSC in the study centre. Out of 101 resuscitated patients who received ROSC, forty three patients (42.5%) were able to maintain it for more than 24 hours. Keywords: in-hospital cardiac arrest, return of spontaneous circulation, prevalence, associated